Peningkatan Proses dan Hasil Belajar Matematika Siswa Melalui Model Pembelajaran Make a Match di Kelas V SDN 064/II Perumnas I - Andika Dimas Saputra; Puput Wahyu Hidayat; Subhanadri Subhanadri (CV. Master Literasi Indonesia, 2025)
This classroom action research aims to describe the improvement of the learning process and mathematics learning outcomes through the implementation of the Make a Match learning model in Grade V students of SDN 064/II Perumnas I, Rimbo Tengah Subdistrict, Bungo Regency. The research was conducted in two cycles, each consisting of the stages of planning, action, observation, and reflection. The research subjects were 18 students, while the focus of the study was on learning activities and mathematics learning outcomes in the topic of decimal number multiplication. Data were collected through observation, learning achievement tests, and documentation, and analyzed using both qualitative descriptive and quantitative approaches. The results showed an increase in student activeness and participation, with the classroom atmosphere becoming more interactive and enjoyable. Student mastery also improved from 27.78% in the initial condition to 66.67% in the first cycle, and further increased to 88.89% in the second cycle. Thus, the Make a Match model proved effective in enhancing both learning activities and mathematics learning outcomes of Grade V students